2008
DOI: 10.1007/s10519-008-9221-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Genetic Background, Gender, and Early Environmental Factors on Isolation-Induced Ultrasonic Calling in Mouse Pups: An Embryo-Transfer Study

Abstract: Infant rodents emit ultrasonic vocalizations when isolated from dam and littermates. Due to the context of their occurrence and the well described bidirectional modulation by substances known for their capability to influence emotionality, it was postulated that such calls reflect a negative affective state akin anxiety. Comparative studies observed pronounced differences in calling behavior between strains, which were paralleled by differences in maternal care. Therefore, it was recently hypothesized that ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 102 publications
(174 reference statements)
4
74
0
1
Order By: Relevance
“…The possible maternal impacts on vocalization may be broadly classified into prenatal versus postnatal effects. Prenatal effects include possibilities as diverse as imprinting of genes inherited maternally, metabolic defects that affect gestational development, or immune responses to the pups during pregnancy (24). Environ-mental stimuli are known to influence vocalization rates, including changes in handling, litter size, and fostering (25,27), and differences in maternal care might affect the environment in which pups are raised and subsequently influence their vocalization rates.…”
Section: Tsc2mentioning
confidence: 99%
“…The possible maternal impacts on vocalization may be broadly classified into prenatal versus postnatal effects. Prenatal effects include possibilities as diverse as imprinting of genes inherited maternally, metabolic defects that affect gestational development, or immune responses to the pups during pregnancy (24). Environ-mental stimuli are known to influence vocalization rates, including changes in handling, litter size, and fostering (25,27), and differences in maternal care might affect the environment in which pups are raised and subsequently influence their vocalization rates.…”
Section: Tsc2mentioning
confidence: 99%
“…In mice, we found similar effects. By conducting an embryo-transfer study, we showed that the isolation-induced calling behaviour in infant mice is highly dependent on early environmental factors such as maternal care [41]. We found that even the closely related mouse strains C57BL/6JOla and C57BL/6N differ in USV production in isolation.…”
Section: Behavioural Neuroscience · Behavioural Phenotyping · Communimentioning
confidence: 90%
“…Interestingly, the sex and developmental stage of offspring influences maternal retrieval behaviours (male pups receive more maternal care than females, and more-developed pups are retrieved sooner than less-developed individuals) (Hahn and Lavooy, 2005), something that may be explained by differences in the calling rate of infant male and female mice (Hahn et al, 1998). Interestingly, maternal responsiveness of a mouse strain is negatively correlated with pup USV calling rate, indicating a close linkage of these behaviours in lab strains (D'Amato et al, 2005;Wöhr et al, 2008). This interaction of maternal response rates and offspring USV production suggests the potential for parent-offspring conflicts, which could be a fruitful area for future research (Box 10.3).…”
Section: Usv Functions In Parent-offspring Communicationmentioning
confidence: 99%
“…A crossfostering study on laboratory mice pups revealed that call features were primarily dependent on the genotype of the pup, and call amplitude was the only feature dependent on the maternal genotype, i.e. on early environmental factors (Wöhr et al, 2008). Another cross-fostering study with BALB and B6 mice, which show strain-specific call types, revealed that adult courtship calls of fostered males remained similar to calls of their genetic parental strain, and did not copy their fostered parents (Kikusui et al, 2011).…”
Section: Pup Vocalizationsmentioning
confidence: 99%